Determinants of Child Labour in Cameroon: A Bivariate Probit Model Analysis - Bikoue, Simeon Maxime (Asian Journal of Economic Modelling, 2021)
The purpose of this article is to highlight the determinants of child labour for children aged 5 to 17 in Cameroon. The study uses microeconomic data from the third Cameroonian household survey (ECAMIII). The bivariate probit model reveals that the risks for a child who works are high if he does not go to school, he is fatherless or both parents are dead, the head of the family is not educated, he works in the agricultural sector, the standard of living of the household is low and he resides in rural areas. The study suggests that the issue of child exploitation in Cameroon is more global and necessarily falls within an economic and social development policy. From this perspective, the strategy to fight the particularly harmful exploitation of child labour should be cross-sectional because of the various dimensions of the phenomenon.